Operational Assessment of Shell and Tube High Pressure Heater in PT Sumber Segara Primadaya's 300 MW Unit 2 Power Plant - Mulyono, Mulyono; Efendi, Erwan Tri; Setiyawan, Rayhan Muhammad Faqi Fikar; Sandi, Dianisa Khoirum; Dhiyaussalam , Dhiyaussalam (Eksergi, 2025)
Electricity is a fundamental necessity, with Indonesia's per capita consumption reaching 1.73 kWh/capita in 2022—a 4% increase from 2021 and the highest in five decades. Projections indicate demand will surge to 1,885 TWh by 2060, with per capita consumption exceeding 5,000 kWh, underscoring the need for efficient power generation. In coal-fired power plants (PLTU), high-pressure shell-and-tube heat exchangers are critical for optimizing efficiency, recovering waste heat to preheat boiler feedwater, reducing fuel use by 5–10%, and minimizing emissions. This study evaluates the performance of these heat exchangers at PT Sumber Segara Primadaya PLTU Cilacap, a major Indonesian PLTU with units totaling 2,260 MW capacity. By analyzing operational effectiveness, this research aims to enhance maintenance strategies and maximize energy output, supporting Indonesia's growing electricity demands while improving thermal efficiency in coal-dependent power systems.